2018
DOI: 10.1002/jcp.26878
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cell–based immunotherapy: From transplantation toward targeting cancer stem cells

Abstract: Natural killer (NK) cells are key players of the innate immune system. NK cells provide protection against infectious pathogens and malignancies in cell. This characteristic may be attributable to their intrinsic diverse potentialities and also their cooperation with adaptive immune lymphocytes, known as B and T cells. The growth, recurrence, and metastasis of cancer cells, and the failure of cytoreductive therapies against cancer cells are due to the small population of intratumor stem-like cells, called canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(33 citation statements)
references
References 120 publications
(236 reference statements)
0
31
0
2
Order By: Relevance
“…Features such as ease of accessibility and separation, high in vitro proliferation capacity, and the ability of differentiation into nonmesodermal lineage lead to its widespread use in regenerative medicine. Tissue repair, secretion of soluble factors resulting in the beneficial therapeutic effect by creating an immunomodulatory environment, selective migration to the tumor site, nonimmunogenic and high ability of genetic modification safely for production of the antitumor agent have become MSCs the best option for targeted gene therapy of cancers (Dianat‐Moghadam, Rokni, Marofi, Panahi, & Yousefi, ; Klinker & Wei, ). MSCs properties and applications are summarized and illustrated in Table and Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Features such as ease of accessibility and separation, high in vitro proliferation capacity, and the ability of differentiation into nonmesodermal lineage lead to its widespread use in regenerative medicine. Tissue repair, secretion of soluble factors resulting in the beneficial therapeutic effect by creating an immunomodulatory environment, selective migration to the tumor site, nonimmunogenic and high ability of genetic modification safely for production of the antitumor agent have become MSCs the best option for targeted gene therapy of cancers (Dianat‐Moghadam, Rokni, Marofi, Panahi, & Yousefi, ; Klinker & Wei, ). MSCs properties and applications are summarized and illustrated in Table and Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Since the first characterization of NK cells, immune cells have been continuously developed for clinical applications in cancer immunotherapy in autologous or allogeneic settings, and there are now an estimated 400 NK cell‐based immunotherapy clinical trials for various types of cancer being conducted worldwide 22 . Despite the numerous ongoing clinical studies involving NK cells and the vast repertoire of historical research reports, infused NK cells have shown short persistency, limited proliferation and inaccurate tumor‐targeting in patients, resulting in poor therapeutic efficacy 23‐27 .…”
Section: Discussionmentioning
confidence: 99%
“…Conventional mAbs may interact with CD16 on NK cells thus enhancing their capability to eliminate CSCs by boosting ADCC. Also, bispecific antibodies are under development in order to improve the physical interaction between NK cells and CSCs …”
Section: Natural Killer Cells and Solid Tumor Derived Cancer Stem Cellsmentioning
confidence: 99%
“…Also, bispecific antibodies are under development in order to improve the physical interaction between NK cells and CSCs. 128…”
Section: And Solid Tumor Derived Cancer Stem Cellsmentioning
confidence: 99%